2018
DOI: 10.3389/fimmu.2018.02818
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans β-Glucan Differentiates Human Monocytes Into a Specific Subset of Macrophages

Abstract: β-Glucan derived from cell walls of Candida albicans is a potent immune modulator. It has been shown to induce trained immunity in monocytes via epigenetic and metabolic reprogramming and to protect from lethal sepsis if applied prior to infection. Since β-glucan-trained monocytes have not been classified within the system of mononuclear phagocytes we analyzed these cells metabolically, phenotypically and functionally with a focus on monocyte-to-macrophage differentiation and compared them with naïve monocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 39 publications
3
44
0
Order By: Relevance
“…Upon rechallenge with a lethal infection of C. albicans, these trained monocytes and macrophages had enhanced cytokine production and improved survival of the infected mice (Browder et al, 1984;Quintin et al, 2012). These host protective effects were confirmed to take place in the absence of T and B cells (Bistoni et al, 1986;Leonhardt et al, 2018). The trained cells also had stronger responses upon restimulation with other microbial antigens and pathogens, including lipopolysaccharide (LPS) and Staphylococcus aureus (Di Luzio and Williams, 1978;Quintin et al, 2012;Marakalala et al, 2013).…”
Section: Trained Immunity: a Second Memory Bank For The Immune Systemmentioning
confidence: 93%
“…Upon rechallenge with a lethal infection of C. albicans, these trained monocytes and macrophages had enhanced cytokine production and improved survival of the infected mice (Browder et al, 1984;Quintin et al, 2012). These host protective effects were confirmed to take place in the absence of T and B cells (Bistoni et al, 1986;Leonhardt et al, 2018). The trained cells also had stronger responses upon restimulation with other microbial antigens and pathogens, including lipopolysaccharide (LPS) and Staphylococcus aureus (Di Luzio and Williams, 1978;Quintin et al, 2012;Marakalala et al, 2013).…”
Section: Trained Immunity: a Second Memory Bank For The Immune Systemmentioning
confidence: 93%
“…Trained immunity arises when some microbial and vaccine antigens cause monocytes/macrophages to make an adaptative response to secondary challenge by increasing their proinflammatory cytokine response to a broad range of microbial stimuli, also known as heterologous protection. This pathogen-agnostic immunity underpins the nonspecific protective effects of the BCG vaccine, among others [37][38][39]. Trained immunity is dependent on epigenetic remodelling and changes in intracellular metabolic pathways.…”
Section: Epigenetic Mechanisms Of Innate Immune Memorymentioning
confidence: 97%
“…As Netea et al points out in his excellent recent review article on TIRIM, models of TRIM using various training agents have shown protection against a host of relevant lethal pathogens such as Streptococcus pneumonia, Toxoplasma gondii, Escherichia coli , and rotavirus ( 43 46 ). Further, the various examples of the BCG vaccine and β-glucan affording protection against secondary infections, such as Candida albicans , in a macrophage specific manner, ultimately leads to the idea that the exposure of innate immune cells, specifically myeloid cells, to specific training stimuli results in a non-specific immune protection ( 7 , 9 , 17 , 47 , 48 ).…”
Section: Trained Innate Immunity (Trim)mentioning
confidence: 99%